Rancangan sistem monitoring kelembapan tanah pembibitan kelapa sawit berbasis internet of things - Effendi, Noverta; Dedi Handoko; Fauzan Azim; Fitri Farida (Computer Science and Information Technology, 2024)
Indonesia is one of the largest palm oil producers in the world, so Indonesia has a role in meeting global demand for palm oil. Indonesia has extensive palm oil plantations in various states, producing around 43 million tons of palm oil. In general, Pekanbaru Riau, in the higher areas the soil is of the Red Yellow Podzolic (PMK) type, while in the lower areas the soil is peat type. PMK mineral soil has a thickness of organic soil material < 60 cm and some of it is still experiencing decomposition so it still contains a lot of fiber so that the agroecosystem on this soil will experience many problems, especially in dry areas with high slopes so that crop cultivation farmers have difficulty measuring soil moisture. Plant seeds cannot live and develop well if soil moisture does not meet requirements. For this reason, it is necessary to fertilize the seeds regularly, on a schedule and have sufficient water available. Based on the problems above, an oil palm tree nursery system was developed using the (Internet of Things) concept. Remote monitoring and control of the tool can be done via an Android application and real time internet access. From the test results of the two tools, namely the soil moisture monitoring system and the moist detector analyzer, the data obtained from soil measurements on oil palm seedlings shows very close measurement values, even from several experiments the data shown is very close, only 1-2%. Of course, from the data displayed the researcher made a comparison with the appropriate/unsuitable information as a reference for the suitability of this tool to be used